Pengendalian Nematoda Parasitik Tanaman secara Hayati dengan Bakteri Pasteuria penetrans: Inventarisasi, Pembiakan Massal, dan Uji Patogenisitas Isolat Bakteri - Mulyadi Mulyadi; B. Triman; Bambang Rahayu TP (Jurnal Perlindungan Tanaman Indonesia, 1995)
The research on “Biological control of plant parasitic nematodes by nematophagous bacteria (Pasteuria penetrans)” was planned to be conducted within 3 years period, started in 1994/1995. In the first year research was done with the following objectives: 1) inventory on the isolates of P. penetrans, and 2) study on the mass production and pathogenicity test of P. penetrans. Survey of P. penetrans was done in the provinces of D.I. Yogyakarta, Central Java, East Java, and West Java. Soil and root samples were collected in this survey, plant parasitic nematodes were isolated using centrifugation and funnel and spray method. Mass production of P. penetrans was done with their host especially root-knot nematodes (Meloidogyne spp.). The bacterial infected nematodes were inoculated on tomato  planted on sterilized soil. Roots contain root-knot nematodes inhabiting spores of P. penetrans were used as inoculum source. The pathogenicity tests of the isolates were done using bioassay method and in the green house in Completely Randomized Design.The research results is as follows: 1) seventeesn isolates of P. penetrans were found in the survey, these isolates were pathogenic to root-knot nematodes, 2) mass production of P. penetrans was done with their host especially root-knot nematodes and 4) treatment with P. penetrans significantly reduced the root-gall caused by root-knot nematodes.